Daktilitas Dinding Panel Semen Eceng Gondok (Emen Wall) - Prasetyo, Lukito (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
This study is a follow-up study to investigate the characteristics of building materials in the form of a wall panel hyacinth (Emen wall). From previous studies, physical properties, mechanical, acoustic and fuel resistance of this material meets the standards of building materials PUBI and ISO 1982 and ASTM C423 03-6861.1-2002-90A. Furthermore, this material will be evaluated by bending test. Beam specimens with dimensions of board 56x35x7cm, will be saddled with the interval until the collapse 100kg. Then note the deflection that occurs based on the work load. From this examination, obtained an average deviation of the ductility factor of 15.04 and the average curvature ductility is 17.10. the kind of collapse of a wall panel material hyacinth (Emen wall) is to be ductile.